PERAN PEREMPUAN DALAM NOVEL TARIAN BUMI KARYA OKA RUSMINI - Yanti, Mira Febri; Hayati, Yenni; Zulfadhli, Zulfadhli (Jurnal Bahasa dan Sastra, 2018)
This study aimed to describe the role of women in the novel Tarian Bumi works Oka Rusmini especially regarding the role of women in family and society.Â  This research is a qualitative research with descriptive method that is verbally describing the problems found in the object of research, the theory used, data analysis, and so on. To examine how the role of women in family and society in the novel, this research is performed the the following steps: (1) analyzing the data by identifying the parts relating to the role of women in the family and society. (2) classify data relating to womenâ€™s roles. (3) interpret data. (4) make conclusions and compile research reports. Based on data analysis, it was concluded that the role of women in the novel Tarian Bumi by Oka Rusmini is as follows. (1) the role of women in the family in the Tarian Bumi novel by Oka Rusmini of: (a) the role of women as children (b) the role of women as mothers (c) the role of women as wives. (2) the role of women in societyKeywords: Gender roles, family and society